Improved Description of a Coordinate Bond in the ReaxFF Reactive Force Field - Pai, Sung Jin; Lee, Hong Woo; Han, Sang Soo (American Chemical Society, 2019)
To improve the description of a coordinate bond of the reactive force field (ReaxFF), we have developed ReaxFF(coord) by explicitly incorporating the coordinate bond contribution, E-coord, into the original ReaxFF (Chenoweth et al. J. Phys. Chem. A 2008, 112, 1040-1053), in which the auxiliary functions are newly suggested to describe the plug-in behavior of lone-pair electrons from a donor atom to a vacant orbital of an acceptor atom. To validate the developed ReaxFF(coord), we tested it in various systems, including a representative coordinate bond-containing molecule, namely, carbon monoxide or ammonia borane. Although the fitting abilities of the ReaxFF(coord) and original ReaxFF are similar, their molecular dynamics (MD) simulations are significantly different, where MD simulations employing ReaxFF(coord) provide more realistic dynamic behaviors of atoms. It is expected that the ReaxFF(coord) will significantly help ReaxFF to successfully extend its applicability to the material and biological systems, including coordinate bonds in organometallic systems.